THE GHADAR MOVEMENT: IGNITING THE FLAME OF FREEDOM IN INDIA - Rashid Manzoor Bhat (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The study attempts to explore the Ghadar Movement, a pivotal revolutionary organisation in the early 20th century that played a significant role in India's struggle for independence. It aims to understand the socio-political origins of the Movement, to analyse its key figures and strategies, to assess its impact on Indian nationalism, and to evaluate its global impact and enduring legacy. The study employs a historical and analytical methodology, using primary and secondary sources to gather data, which is then interpreted and contextualised. In-depth examination of archival documents revealed the influences of colonial oppression, global events, and the sentiments of the Indian diaspora in igniting the Ghadar Movement. The study identifies key figures, their motivations and the strategies they employed, such as direct revolts and protests, as well as indirect approaches like propaganda and international networking. The research finds that the Ghadar Movement significantly influenced the rise of Indian nationalism and other revolutionary movements, shaping the course of India's freedom struggle. It also managed to garner notable international support, leaving a lasting impact beyond India's borders. It finds that the movement though unsuccessful in its immediate goals, left an indelible legacy in post-independence India, influencing its socio-political fabric and contributing to the narrative of India's struggle for independence.